Frailty is the New Age: A Retrospective Study of Modified Frailty Index for Preoperative Risk Assessment in Autologous Breast Reconstruction - Chow, Amanda L.; Karius, Alexander K.; Broderick, Kristen P.; Cooney, Carisa M. (Journal of Reconstructive Microsurgery, 2023)
Background Age is a poor predictor of postoperative outcomes in breast reconstruction necessitating new methods for risk-stratifying patients preoperatively. The 5-item modified frailty index (mFI-5) is a validated measure of frailty which assesses patients' global health. The purpose of this study was to compare the effectiveness of mFI-5 and age as independent predictors of 30-day postoperative complications following autologous breast reconstruction.Methods Patients who underwent autologous breast reconstruction between 2005 and 2019 were identified from the American College of Surgeons National Surgical Quality Improvement Program. Patients were stratified based on presence of major, minor, both minor and major, and no complications. Univariate and multivariate logistic regression were performed to determine the predictive power of mFI-5, age, and other preoperative risk factors for development of minor and major 30-day postoperative complications in all patients and stratified by flap type.Results A total of 25,215 patients were included: 20,366 (80.8%) had no complications, 2,009 (8.0%) had minor complications, 1,531 (6.1%) had major complications, and 1,309 (5.2%) had both minor and major complications. Multivariate regression demonstrated age was not a predictor of minor (odds ratio [OR]: 1.0, p = 0.045), major (OR: 1.0, p = 0.367), or both minor and major (OR: 1.0, p = 0.908) postoperative complications. mFI-5 was a significant predictor of minor complications for mFI-5 scores 1 (OR: 1.3, p < 0.001), 2 (OR: 1.8, p < 0.001), and 3 (OR: 2.8, p = 0.043). For major complications, mFI-5 was a significant predictor for scores 1 (OR: 1.2, p = 0.011) and 2 (OR: 1.3, p = 0.03).Conclusion Compared with age, mFI-5 scores were better predictors of 30-day postoperative complications following autologous breast reconstruction regardless of flap type. Additionally, higher mFI-5 scores were associated with increased odds of minor and major complications. Our findings indicate that reconstructive breast surgeons should consider using the mFI-5 in lieu of age to risk-stratify patients prior to autologous breast reconstruction surgery.
Keywords: breast reconstruction; autologous breast reconstruction; frailty; frailty index; age